Family Firm Heterogeneity and its Effect on Strategy. The Case of the Spanish Wine Sector - Abella-Garcés, Silvia; Ferrer, Juan Ramón (European Journal of Family Business, 2022)
This research aims to cover some of the existing gap in the strategy of family firms literature, taking into account the heterogeneity of this kind of firms. We use a logit regression methodology in order to analyse the relationship between the strategy selected by the family firm and its performance, and whether differences exist depending on the degree of the family involvement in the firm. In order to test for our hypothesis, we use a sample of Spanish firms from the wine sector. Our results show that Porter’s cost strategy is positively related to performance for all type of family firms, and that a Miles’ analyser strategy is positively related to performance in family firms, although the effect of this strategy loses its impact as the degree of involvement of the family in the firm increases. It has also been shown that Miles’ reactive strategy, in family firms with more than fifty per cent of family involvement, negatively influences performance. In short, the results show that the strategy chosen by the family firm depends on the degree of property owned by the family.